Cerebrospinal Fluid Analysis in Recumbent Adult Dairy Cows With or Without Spinal Cord Lesions. (6th April 2017) - Achard, D.; Francoz, D.; Grimes, C.; Desrochers, A.; Nichols, S.; Babkine, M.; Fecteau, G.
Abstract : Background: Diagnosis of central nervous system (CNS) lesions in recumbent dairy cattle (RDC) is challenging because neurologic examination is limited and medical imaging often is challenging or unrewarding. Cerebrospinal fluid (CSF) analysis is useful in the diagnosis of CNS disorders in cattle. However, its utility in identifying spinal cord lesions in RDC remains to be evaluated. Hypothesis/Objectives: We hypothesized that CSF analysis would discriminate between RDC with and without spinal cord lesions. Animals: Twenty‐one RDC with spinal cord lesions (RDC+) and 19 without (RDC−) were evaluated. Methods: Spinal cord lesions were confirmed at necropsy. Signalment, clinical findings, and CSF results were compared retrospectively. Total nucleated cell count and differential, protein concentration, and red blood cell count in RDC+ and RDC− were compared. Results: Neoplasia, trauma, and infectious processes were the most frequent spinal cord lesions identified. Cerebrospinal fluid protein concentrations and TNCC were significantly higher in RDC+ compared to RDC− ( P = .0092 and P = .0103, respectively). Additionally, CSF protein concentrations and TNCC in RDC− were lower than previously published reference ranges. Using an interpretation rule based on CSF protein concentration and TNCC, it was possible to accurately identify 13 RDC with spinal cord lesions and 6 RDC without lesions. It was not possible to determine spinal cord status in the remaining 18 RDC. Conclusions and Clinical Importance: Cerebrospinal fluid analysis is valuable in the evaluation of spinal cord status in RDC. The prognosis associated with these findings remains to be determined.